Providing baseline data for conservation–Heart rate monitoring in captive scimitar-horned oryx - Leimgruber, Peter; Songsasen, Nucharin; Stabach, Jared A.; Horning, Megan; Reed, Dolores; Buk, Tara; Harwood, Arielle; Layman, Lawrence; Mathews, Christopher; Vance, Morgan; Marinari, Paul; Helmick, Kelly E.; et al. (Frontiers in Physiology, 2023)
Heart rate biologging has been successfully used to study wildlife responses to natural and human-caused stressors (e.g., hunting, landscape of fear). Although rarely deployed to inform conservation, heart rate biologging may be particularly valuable for assessing success in wildlife reintroductions. We conducted a case study for testing and validating the use of subcutaneous heart rate monitors in eight captive scimitar-horned oryx (Oryx dammah), a once-extinct species that is currently being restored to the wild. We evaluated biologger safety and accuracy while collecting long-term baseline data and assessing factors explaining variation in heart rate. None of the biologgers were rejected after implantation, with successful data capture for 16–21 months. Heart rate detection accuracy was high (83%–99%) for six of the individuals with left lateral placement of the biologgers. We excluded data from two individuals with a right lateral placement because accuracies were below 60%. Average heart rate for the six scimitar-horned oryx was 60.3 ± 12.7 bpm, and varied by about 12 bpm between individuals, with a minimum of 31 bpm and a maximum of 188 bpm across individuals. Scimitar-horned oryx displayed distinct circadian rhythms in heart rate and activity. Heart rate and activity were low early in the morning and peaked near dusk. Circadian rhythm in heart rate and activity were relatively unchanged across season, but hourly averages for heart rate and activity were higher in spring and summer, respectively. Variation in hourly heart rate averages was best explained by a combination of activity, hour, astronomical season, ambient temperature, and an interaction term for hour and season. Increases in activity appeared to result in the largest changes in heart rate. We concluded that biologgers are safe and accurate and can be deployed in free-ranging and reintroduced scimitar-horned oryx. In addition to current monitoring practices of reintroduced scimitar-horned oryx, the resulting biologging data could significantly aid in 1) evaluating care and management action prior to release, 2) characterizing different animal personalities and how these might affect reintroduction outcomes for individual animals, and 3) identifying stressors after release to determine their timing, duration, and impact on released animals. Heart rate monitoring in released scimitar-horned oryx may also aid in advancing our knowledge about how desert ungulates adapt to extreme environmental variation in their habitats (e.g., heat, drought).